Sporothrix schenckii complex biology: environment and fungal pathogenicity - Téllez Martínez, Damiana [UNESP]; Batista-Duharte, Alexander [UNESP]; Portuondo, Deivys [UNESP]; Quinello, Carolina [UNESP]; Bonne-Hernandez, R.; Carlos, Iracilda Zeppone [UNESP] (Soc General Microbiology, 2014)
Sporothrix schenckii is a complex of various species of fungus found in soils, plants, decaying vegetables and other outdoor environments. It is the aetiological agent of sporotrichosis in humans and several animals. Humans and animals can acquire the disease through traumatic inoculation of the fungus into subcutaneous tissue. Despite the importance of sporotrichosis, it being currently regarded as an emergent disease in several countries, the factors driving its increasing medical importance are still largely unknown. There have only been a few studies addressing the influence of the environment on the virulence of these pathogens. However, recent studies have demonstrated that adverse conditions in its natural habitats can trigger the expression of different virulence factors that confer survival advantages both in animal hosts and in the environment. In this review, we provide updates on the important advances in the understanding of the biology of Spor. schenckii and the modification of its virulence linked to demonstrated or putative environmental factors.